Research on the recycling of waste activated sludge as an adsorbent material for ammonium removal in wastewater - Tuan Minh, Nguyen; Van Tuyen, Trinh; Thi Phuong Thao, Nguyen; Huu Tung, Pham; Minh Viet, Trinh (Vietnam Journal of Science and Technology, 2022)
Waste activated sludge is an abundant byproduct of wastewater treatment plants considered to be a secondary pollutant due to its large amount and unmanageable production. Recently, reports about preparing sludge-derived activated carbon or activated sludge as a new adsorbent material, which is also a new alternative sludge treatment without causes secondary pollution. In this study, the sludge-derived activated carbon or activated sludge was fabricated from the sludge generated by the WWTPs in an industrial brewery through a pyrolysis technique to achieve a new adsorbent for ammonium removal. The sludge-based biochar samples possessed better porous structure, larger specific surface area and pore size comparing to the dried sludge sample. Batch adsorption experiments were also conducted to investigate the removal efficiency and adsorption capacity of the ammonium. The results showed that the operating conditions for ammonium adsorption were optimized at BS400 (400 oC-pyrolyzed sludge) dosage of 20 g/L, initial ammonium concentration of 30 mg/L at pH 6 in a total contact time of 120 min. The experimental data were best fitted the Langmuir isotherm, while the kinetic was followed the pseudo-second-order model. The column adsorption showed that 10g of BS400 could maintain 375 mL and 1050 mL of 20mg/L and 10mg/L NH4+ solution to meet the NH4+ threshold in National Technical Regulation on Industrial wastewater (QCVN40:2021/BTNMT) with the adsorption capacity of 0.642 and 0.784 mg/g, respectively.